Clinical evaluation of the implementation of the first pilot Russian integrated program for an integrated approach to the management of diabetes mellitus “NORMA” - G. R. Galstyan; A. Y. Mayorov; O. G. Melnikova; N. I. Holmskaya; Z. A. Hamradjanov; V. I. Milyutin; M. V. Shestakova (Сахарный диабет)
BACKGROUND: Despite progress in the treatment of patients with diabetes mellitus (DM), the problem of achieving target values of glycemic control remains relevant. In this regard, the search for new integrated solutions that could strengthen disease control and improve clinical outcomes becomes relevant.AIM: To assess the impact of the developed integrated approach to disease management on the clinical and metabolic outcomes of patients with type 1 (T1DM) and type 2 diabetes mellitus (T2DM) participating in the “NORMA” pilot program for 3 and 6 months.MATERIALS AND METHODS: “NORMA” is the first Russian program designed to implement an integrated approach to DM management combines structured online education, blood glucose monitoring, supervision by endocrinologist, and administrative support. Interium retrospective analysis analysis of pre-existing data generated in the Program was performed from October 2020 to November 2021. Adults (≥18 years) with uncontrolled T1DM or T2DM on insulin (HbA1c>7,0%) with duration of DM ≥6 months were included. The following characteristics were considered: social-demographic parameters, duration of DM, complications, HbA1c, hypoglycemia events, daily insulin dose, patients’ perception of DM checklist (scaled 1-10), level of DM knowledge (questionnaire of 20 points).RESULTS: Data from 185 persons were analyzed: 132 with T1DM and 53 with T2DM, 67% women, the mean age was 41.3±14.4 years; the median DM duration was 12.0 [6.0; 19.0] years, 30 persons (16.3%) were free of any DM complications. Mean HbA1c decreased from 8.8±1.5% to 7.4±1.2% at month 3, and to 7.6±1.5% at month 6 (p<0.001). HbA1c <7.0% was achieved in 38.9% and 38.1% participants after 3 and 6 months, respectively. The total insulin dose has not changed within the program. The DM knowledge level after 3 months of Program increased significantly by 25.4±15.0% (p<0.001). The mean scores of patients’ perceptions of DM after 3 and 6 months increased by 2.1±10.2 % and 2.4±11.0 % (p<0.01), but the median scores (interquartile range) did not change: 0.00% (-3.00–6.00%) and 0.50% (-3.00–9.00%) respectively.CONCLUSION: In a real-life setting, the implementation of an integrated approach to the diabetes management was associated with the improvement of glycemic control without significant changes of total insulin dose.